The Effect Of Good Corporate Governance Mechanism On The Financial Perofrmance Of Registered Banking Companies On The Stock Exchange - Yolanda Permatasari Nababan (International Journal of Applied Finance and Business Studies, 2021)
Corporate governance remains a major problem during the post-financial crisis period in the growing Asian markets like Indonesia. In particular, financial institutions have adopted corporate governance reforms to improve the protection of the interests of shareholders and stakeholders. The purpose of this study was to measure the corporate governance and performance in the banking sector which specifically determine a mechanism of corporate governance. This research is replicated frame the prior researchs. The difference is solely on the theoretical concept change. Independent variables used in this study is the size of the board of directors, the size of the board of commissioners, and independent commissioner. The dependent variable used in this study is banking performance (ROA). Samples from this study is the general banking company located in Indonesia are listed in the Indonesia Stock Exchange (IDX) in the period 2008-2010. This research data come from bank annual reports (annual report) in the period 2008-2010 obtained from the Indonesian Stock Exchange website, the Indonesian Banking Directory, Indonesian Capital Market Directory (ICMD). The analytical method used is multiple linear regression in accordance with the purpose of research which analyzes the influence of independent variables on the dependent variable. Purposive sampling method is used to determine the sample selection. From this method, obtained 26 samples of commercial banks. The total observing period is three years, so the total sample is 60 observations. The study shows that the size of the board of directors and size of the board of commissioners is a positive but not significant to banking performance. Second, the independent commissioners addressing negative and not significant to banking performance.